Case Report: Ocular metastasis from ALK-rearranged pulmonary adenocarcinoma presenting as a pseudo-syndrome of anterior uveitis - Zhao, Cong; Chen, Jiaqi; Liu, Hongji; Dai, Yan (Frontiers in Oncology, 2025)
Lung cancer is the second most common primary site for intraocular metastatic tumors, with the most frequent metastatic site being the choroid. However, cases of intraocular metastasis of lung cancer presenting as anterior uveitis or secondary glaucoma are rare and often misdiagnosed. Here, we report a case of a lung adenocarcinoma stage IV patient, who presented with anterior uveitis as the initial symptom without respiratory symptoms. After 28 months of follow-up, the patient received targeted treatment with Alectinib hydrochloride capsules and a series of timely ophthalmic surgeries. Following these treatments, the patient’s intraocular and intracranial metastatic lesions disappeared, the primary pulmonary lesion significantly shrank, and the best corrected visual acuity (BCVA) improved from HM/30cm to 1.0. No significant toxic side effects were observed during the treatment, and the prognosis was favorable. The patient is currently living and working normally without complications. This case highlights the importance of considering metastatic tumors in patients with refractory anterior uveitis. Combined multimodal imaging and fluid biopsy can improve the early diagnosis rate of intraocular metastases. Targeted therapy based on genetic mutation detection, along with the appropriate timing for ophthalmic surgery, is crucial for improving patient prognosis.